Construct Validity and Reliability of The Nomophobia Scale in High School Students - Novi Yanti Pratiwi; Wanda Eka Saputri; Siti Murdiana (Universitas Negeri Makassar, 2026)
Nomophobia (no mobile phone phobia) refers to excessive anxiety experienced when individuals are unable to use or access their smartphones, an issue that has become increasingly prevalent among adolescents due to their growing dependence on mobile devices. This study aimed to examine the validity and reliability of the Nomophobia Scale among senior high school students. The participants consisted of 441 students (243 females and 198 males), aged 15–18 years, from Grades 10, 11, and 12, who were selected using accidental sampling. Construct validity was assessed using Confirmatory Factor Analysis (CFA) and item-rest correlation, while reliability was evaluated using Cronbach's alpha and McDonald's omega coefficients. The CFA results indicated that all 20 items demonstrated adequate factor loadings (0.448–0.737), with the measurement model showing good fit indices (CFI = 0.929; TLI = 0.907; RMSEA = 0.061). The item discrimination analysis showed that all items were valid (item-rest correlation ≥ 0.300, ranging from 0.403 to 0.651). The scale also demonstrated excellent internal consistency reliability (Cronbach's α = 0.912; McDonald's ω = 0.914). These findings indicate that the Nomophobia Scale is a valid and reliable instrument for assessing nomophobia among senior high school students. Keywords: confirmatory factor analysis; nomophobia; reliability; senior high school students; validity